UTILIZATION OF PINE FRUIT (Pinus mercusii) AS RAW MATERIAL FOR ENVIRONMENTALLY FRIENDLY BIOPESTICIDE FOR SPINACH PLANTS - Indhasari, Fitri; Putra, Muh. Mukhtadir; Achmad, Fadhilah (Universitas Gorontalo, 2025)
This research aims to find out the best formulation of pine cones in making biopesticides, find out the processing of pine waste in overcoming pest problems in spinach plants and the growth of spinach plants that have been given biopesticide made from pine cones. biopesticide standard. The treatment used was a combination of biopesticide and pine cones with a ratio of L0 = control (without biopesticide), L1 = 1:10:3:1, L2 = 1:10:3:3, L3 = 1:10:3:6, Each treatment was repeated 3 times. Making biopesticide uses 250 ml of acetone solution, 6 liters of clean water, and pine fruit waste according to a predetermined formulation. It is hoped that the results of this research will be able to utilize pine cones in everyday life to become an economically valuable product to ensure the fulfillment of food needs in supporting food security and independence programs.